JOB SATISFACTION AND RELATED FACTORS OF INPATIENT NURSES AT VUNG TAU GENERAL HOSPITAL IN 2025 (Vietnam Journal of Community Medicine, 2026)
The research was conducted to determine the job satisfaction and related factors of nurses taking care of inpatients at the hospital in 2025. The data collected were questionnaires from 155 nurses directly involved in taking care of inpatients at the clinical departments of Vung Tau Hospital. The study was conducted with a cross-sectional descriptive design from May 2025 to July 2025. The results showed that 74.8% of inpatient nurses at the Hospital were satisfied with their jobs. The aspect with the highest satisfaction rate was the relationship with colleagues (98.7%), the aspect with the lowest satisfaction rate was working conditions (27.1%). Factors significantly related to job characteristics were working less than 48 hours/week, seniority of nurses and number of times on duty from 1-4 times/month.
Keywords: Satisfaction, inpatients, related factors.